Studi Metode Perkuatan Lereng Menggunakan Soil Nailing Dan Shotcrete (Studi Kasus: Lereng Off Ramp Karawang Barat Pada Ruas Jalan Tol Jakarta -Cikampek ) - Fento Hara; Abdul Rochim; Sumirin (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Landslides that occur on slopes can be caused by several influences, both human and natural influences. There are also several ways to handle slopes, adjusting the type of soil at the handling location and its function and purpose. The reinforcement method using Soil Nailing and shotcrete is one alternative choice for strengthening slopes. The purpose of this study is to determine the value of the safety factor of the existing slope before reinforcement with Soil Nailing and shotcrete and the value of the safety factor of the slope after reinforcement with Soil Nailing and shotcrete on the slope of the West Karawang Off Ramp, Jakarta - Cikampek Toll Road. Slope stability analysis using the Plaxis.2D program (finite element method). At this stage, the existing conditions are analyzed for slope stability with a pavement load of 10 kPa and earthquake loads.The results of the analysis of the existing slope before reinforcement with Soil Nailing and Shotcrete, the condition of the existing embankment is still with a safety factor value in the short-term condition of no water level (dry) namely (SF = 1.328) > 1.30 safe (Stable) in the safety factor condition C = 0 seismic / earthquake collapse occurs (SF = 0.88) < 1.0 has the potential for landslides (unsafe) and the safety factor in the long-term condition of water-saturated conditions is (SF = 1.221) < 1.50 has the potential for landslides (unsafe) So the slope needs to be repaired and strengthened. Analysis Results after reinforcement using Soil Nailing and Shotcrete, the results of the slope stability analysis showed a short-term safety factor for short-term conditions without water level (dry) namely (SF = 1.823)> 1.30 Safe (stable), in the safety factor for section C = 0 seismic / earthquake conditions namely (SF = 1.130)> 1.0 safe (stable) and the safety factor for long-term conditions (Saturated water) namely (SF = 1.759)> 1.50 Safe (stable).